Effects of hepatocyte nuclear factor-1A and -4A on pancreatic stone protein/regenerating protein and C-reactive protein gene expression: implications for maturity-onset diabetes of the young - Kyithar, Ma P (BioMed Central, 2013)
BACKGROUND: There is a significant clinical overlap between patients with hepatocyte nuclear factor (HNF)-1A and HNF4A maturity-onset diabetes of the young (MODY), two forms of monogenic diabetes. HNF1A and HNF4A are transcription factors that control common and partly overlapping sets of target genes. We have previously shown that elevated serum pancreatic stone protein / regenerating protein A (PSP/reg1A) levels can be detected in subjects with HNF1A-MODY. In this study, we investigated whether PSP/reg is differentially regulated by HNF1A and HNF4A. METHODS: Quantitative real-time PCR (qPCR) and Western blotting were used to validate gene and protein expression in cellular models of HNF1A- and HNF4A-MODY. Serum PSP/reg1A levels and high-sensitivity C-reactive protein (hsCRP) were measured by ELISA in 31 HNF1A- and 9 HNF4A-MODY subjects. The two groups were matched for age, body mass index, diabetes duration, blood pressure, lipid profile and aspirin and statin use. RESULTS: Inducible repression of HNF1A and HNF4A function in INS-1 cells suggested that PSP/reg induction required HNF4A, but not HNF1A. In contrast, crp gene expression was significantly reduced by repression of HNF1A, but not HNF4A function. PSP/reg levels were significantly lower in HNF4A subjects when compared to HNF1A subjects [9.25 (7.85-12.85) ng/ml vs. 12.5 (10.61-17.87) ng/ml, U-test P = 0.025]. hsCRP levels were significantly lower in HNF1A-MODY [0.22 (0.17-0.35) mg/L] compared to HNF4A-MODY group [0.81 (0.38-1.41) mg/L, U-test P = 0.002], Parallel measurements of serum PSP/reg1A and hsCRP levels were able to discriminate HNF1A- and HNF4A-MODY subjects. CONCLUSION: Our study demonstrates that two distinct target genes, PSP/reg and crp, are differentially regulated by HNF1A and HNF4A, and provides clinical proof-of-concept that serum PSP/reg1A and hsCRP levels may distinguish HNF1A-MODY from HNF4A-MODY subjects.